2017
DOI: 10.1177/1010428317694547
|View full text |Cite
|
Sign up to set email alerts
|

Decreased RNA-binding motif 5 expression is associated with tumor progression in gastric cancer

Abstract: RNA-binding motif 5 is a putative tumor suppressor gene that modulates cell cycle arrest and apoptosis. We recently demonstrated that RNA-binding motif 5 inhibits cell growth through the p53 pathway. This study evaluated the clinical significance of RNA-binding motif 5 expression in gastric cancer and the effects of altered RNA-binding motif 5 expression on cancer biology in gastric cancer cells. RNA-binding motif 5 protein expression was evaluated by immunohistochemistry using the surgical specimens of 106 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Many other RBPs also exhibit changed expression in GC tissues. The hnRNP‐A1, ‐A2/B1, ‐C, ‐F, ‐K, polypyrimidine tract‐binding protein (PTBP)‐1, ‐3, poly r(C) binding protein 2, IMP‐3, Musashi‐1, and non‐POU domain containing octamer binding protein (NONO) were upregulated (C. Chen et al, ; Huang et al, ; Jing et al, ; P. T. Lee et al, ; D. Li et al, ; Park et al, ; Shou et al, ; Sugiyama et al, ; S. H. Xu et al, ; R. Yang et al, ; Zhou et al, ), while RNA‐binding motif (RBM)‐4, ‐5, RBM single‐stranded interacting protein 3 (RBMS3), and PCBP1 were inhibited (Ji et al, ; Kobayashi et al, ; Y. Wu et al, ; Yong et al, ; T. Zhang et al, ). These aberrant expression patterns were thought to associate with pathologic feature and survival of GC patients, but further investigations are needed to reveal their functions and direct targets during cancer development.…”
Section: Major Functions Of Rbps In Gi Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Many other RBPs also exhibit changed expression in GC tissues. The hnRNP‐A1, ‐A2/B1, ‐C, ‐F, ‐K, polypyrimidine tract‐binding protein (PTBP)‐1, ‐3, poly r(C) binding protein 2, IMP‐3, Musashi‐1, and non‐POU domain containing octamer binding protein (NONO) were upregulated (C. Chen et al, ; Huang et al, ; Jing et al, ; P. T. Lee et al, ; D. Li et al, ; Park et al, ; Shou et al, ; Sugiyama et al, ; S. H. Xu et al, ; R. Yang et al, ; Zhou et al, ), while RNA‐binding motif (RBM)‐4, ‐5, RBM single‐stranded interacting protein 3 (RBMS3), and PCBP1 were inhibited (Ji et al, ; Kobayashi et al, ; Y. Wu et al, ; Yong et al, ; T. Zhang et al, ). These aberrant expression patterns were thought to associate with pathologic feature and survival of GC patients, but further investigations are needed to reveal their functions and direct targets during cancer development.…”
Section: Major Functions Of Rbps In Gi Cancermentioning
confidence: 99%
“…H. Xu et al, 2018;R. Yang et al, 2016;, while RNA-binding motif (RBM)-4, -5, RBM single-stranded interacting protein 3 (RBMS3), and PCBP1 were inhibited (Ji et al, 2017;Kobayashi et al, 2017;Yong et al, 2016;. These aberrant expression patterns were thought to associate with pathologic feature and survival of GC patients, but further investigations are needed to reveal their functions and direct targets during cancer development.…”
Section: Function Of Rbps In Gastric Cancermentioning
confidence: 99%
“…RBM5 is a ubiquitously expressed RBP known to regulate mRNA and protein levels, as well as alternative splicing of genes involved in regulation of apoptosis, cell cycle, cytoskeleton, and drug metabolism 43 , 69 , 73 , 85 87 . RBM5 can both stimulate and suppress splicing at specific splice sites via different mechanisms 41 , 42 , 67 , 69 , 72 , 88 .…”
Section: Discussionmentioning
confidence: 99%
“…RBPs also play a vital role in the initiation of GC. It was reported that RBM5 downregulation was involved in GC progression, behaving as a tumor suppressor gene in GC ( 19 ). RBPs have the potential to be used as novel biomarkers as well.…”
Section: Discussionmentioning
confidence: 99%